Preferential Mapping of Sex-Biased Differentially-Expressed Genes of Larvae to the Sex-Determining Region of Flathead Grey Mullet (Mugil cephalus) - Dor, Lior; Shirak, Andrey; Curzon, Arie Y.; Rosenfeld, Hana; Ashkenazi, Iris M.; Nixon, Oriya; Seroussi, Eyal; Weller, Joel I.; Ron, Micha (Frontiers in Genetics, 2020)
Flathead grey mullet (Mugil cephalus) is a cosmopolitan mugilid species popular in fishery and aquaculture with an economic preference for all-female population. However, it displays neither sexual dimorphisms nor heteromorphic sex chromosomes. We have previously presented a microsatellite-based linkage map for this species locating a single sex determination region (SDR) on linkage group 9 (LG9) with evidence for XX/XY sex determination (SD) mechanism. In this work, we refine the critical SDR on LG9, and propose positional- and functional- candidate genes for SD. To elucidate the genetic mechanism of SD, we assembled and compared male and female genomic sequences of 19 syntenic genes within the putative SDR on mullet’s LG9, based on orthology to tilapia’s LG8 (tLG8) physical map. A total of 25 sequence-based markers in 12 genes were developed. For all markers, we observed association with sex in at least one of the two analyzed M. cephalus full-sib families, but not in the wild-type population. Recombination events were inferred within families thus setting the SDR boundaries to a region orthologous to ~0.9 Mbp with 27 genes on tLG8. As the sexual phenotype is evident only in adults, larvae were assigned into two putative sex-groups according to their paternal haplotypes, following a model of XY/XX SD-system. A total of 107 sex-biased differentially-expressed genes in larvae were observed, of which 51 were mapped to tLG8 (48% enrichment), as compared to 5% in random control. Furthermore, 23 of the 107 genes displayed sex-specific expression; and 22 of these genes were positioned to tLG8, indicating 96% enrichment. Of the 27 SDR genes, BCCIP, DHX32A, DOCK1 and FSHR (GTH-RI) are suggested as positional and functional gene candidates for SD.